A valid and reliable method to measure jump‐specific training and competition load in elite volleyball players. (8th February 2018) - Skazalski, C.; Whiteley, R.; Hansen, C.; Bahr, R.
Abstract : Use of a commercially available wearable device to monitor jump load with elite volleyball players has become common practice. The purpose of this study was to evaluate the validity and reliability of this device, the Vert, to count jumps and measure jump height with professional volleyball players. Jump count accuracy was determined by comparing jumps recorded by the device to jumps observed through systematic video analysis of three practice sessions and two league matches performed by a men's professional volleyball team. Jumps performed by 14 players were each coded for time and jump type and individually matched to device recorded jumps. Jump height validity of the device was examined against reference standards as participants performed countermovement jumps on a force plate and volleyball‐specific jumps with a Vertec. The Vert device accurately counted 99.3% of the 3637 jumps performed during practice and match play. The device showed excellent jump height interdevice reliability for two devices placed in the same pouch during volleyball jumps ( r  = .99, 95% CI 0.98‐0.99). The device had a minimum detectable change (MDC) of 9.7 cm and overestimated jump height by an average of 5.5 cm (95% CI 4.5‐6.5) across all volleyball jumps. The Vert device demonstrates excellent accuracy counting volleyball‐specific jumps during training and competition. While the device is not recommended to measure maximal jumping ability when precision is needed, it provides an acceptable measure of on‐court jump height that can be used to monitor athlete jump load.